Resistência e poesia negra: uma leitura de “poemas da recordação e outros movimentos”, de Conceição Evaristo - (:unkn) unknown (Brasil, 2025)
This article aims to analyze Conceição Evaristo’s contribution to Afro-Brazilian literature, highlighting her representation of Afro-Brazilian identity and the social, racial, and gender issues present in her works. The research was conducted through a bibliographic review, which included books, academic articles, and interviews with the author. The analyses focused on Conceição Evaristo’s work Poemas da recordação e outros movimentoes (2017), focusing on the way in which her texts, especially her poems, address the experience of black women in contemporary Brazil. The aim is to highlight how the author uses literature as a tool of resistance and empowerment, promoting a critical reflection on racial and social inequalities. The study aims to contribute to the appreciation of Afro-Brazilian literature and to increase the visibility of Afro-descendant voices in literary production. Conceição Evaristo is a central figure in contemporary literature, whose works challenge stereotypes and promote cultural diversity. Her writing not only enriches Brazilian literature, but also represents a powerful means of fighting for and affirming black identity, offering new perspectives on the social reality of Brazil. This research is based on possible readings, interpretations from a point of view in which racial prejudice and the injustices suffered by black female bodies will be the basis of discussion, in line with Conceição Evaristo’s poetic construction. The aim was, albeit minimally, to provide a sensitive reading that is not exhaustive, but rather prompts new analyses.
Resistance and black poetry: a reading of “poemas of memory and other movements”, by Conceição Evaristo
Keywords: Literatura negro-brasileira; Conceição Evaristo; Identidade afro-brasileira; Black-Brazilian literature; Afro-Brazilian identity; letras